Study Effects of Illumination and Temperature on Performance of (pn-Si) Device using Simulation Program SCAPS-1D - Rasool, Raad; Mohammed, Ali A; Hasan, Rasha F. (Iraqi Journal of Science, 2021)
The current research included obtaining the best performance specifications for a silicon device with a mono-crystalline type pn junction (pn–Si). A simulation of the device was performed by the use of a computer program in one dimension SCAPS-1D in order to reach the optimum thickness for both p and n layers and to obtain the best efficiency in performance of the pn-Si junction. The optimum device efficiency was eta (η) = 12.4236 % when the ideal thickness for the p and n layers was 5µm and 1.175µm, respectively (p=5 µm and n=1.75µm). The research included studying the effects of different spectra of solar illumination using simulation of the device; the usual solar spectrum AM1_5 G1 sun. Spectrum, Black body spectrum, White spectrum constant photon flux, White spectrum constant photon power, Monochromatic spectrum constant flux, and Monochromatic spectrum constant power. The highest efficiency was obtained from the monochrome spectrum with constant power (eta (η) =22.4338 %). The effects of different temperatures on the device was studied on 250K, 300K, 350K, 400K, and 450K. The highest efficiency was revealed for Monochromatic spectrum constant power (eta (η) =24.5381 %) when the temperature was 250K.